Development and validation of lactic acid starter cultures for enset (Ensete ventricosum) fermentation. (November 2019) - Andeta, Addisu Fekadu; Teffera, Fassil Eshetu; Misganaw, Fantahun Woldesenbet; Borremans, An; Vandeweyer, Dries; De Smedt, Anneke; Bossaert, Sofie; Crauwels, Sam; Lievens, Bart; Vancampenhout, Karen; Van Campenhout, Leen
Abstract: In this study, lactic acid bacteria strains were screened for the development of (a) starter culture(s) specific for enset ( Ensete ventricosum ) fermentation. To this end, 158 isolates grown on de Man, Rogosa and Sharpe agar were obtained from fermenting enset and traditional starter material. They were screened based on their biochemical characteristics. Three promising strains, two Lactobacillus plantarum and one Leuconostoc mesenteroides, were selected and evaluated under field conditions. Aliquots of pulverized enset (without adding a liquid) were inoculated with one of the isolates at 3 log cfu/g and one uninoculated portion was used as control. Fermentation was performed in sauerkraut jars. Samples were taken on days 0, 7, 15, 30 and 75. On day 7 and onwards, the inoculated samples showed a larger pH reduction compared to the control. Enterobacteriaceae counts were reduced below the detectable level on day 7 and onwards. Clostridium spore counts were significantly lower for the inoculated than for the uninoculated samples on day 75. Inoculated enset showed a faster colonization of lactic acid bacteria than the uninoculated biomass. The three starters appeared to be suitable for enset fermentation. Further research is necessary to elucidate the proximate composition of enset fermented with these starters. Highlights: In Ethiopia, enset is fermented into kocho which is consumed as daily bread. Lactic acid bacteria were isolated from enset plants and artisanal starter material. The amylolytic activity and growth of the isolates in enset extract were determined. Potential starter cultures for enset fermentation were selected and identified. They improved the pH reduction and microbial composition during field fermentation.